Understanding geographical variations in health system performance: a population-based study on preventable childhood hospitalisations - Daniel Exeter; Pushkar Raj Silwal; Arier Lee; Tim Tenbensel (BMJ Open)
Objective To investigate interdistrict variations in childhood ambulatory sensitive hospitalisation (ASH) over the years.Design Observational population-based study over 2008–2018 using the Primary Health Organisation Enrolment Collection (PHO) and the National Minimum Dataset hospital events databases.Setting New Zealand primary and secondary care.Participants All children aged 0–4 years enrolled in the PHO Enrolment Collection from 2008 to 2018.Main outcome measure ASH.Results Only 1.4% of the variability in the risk of having childhood ASH (intracluster correlation coefficient=0.014) is explained at the level of District Health Board (DHB), with the median OR of 1.23. No consistent time trend was observed for the adjusted childhood ASH at the national level, but the DHBs demonstrated different trajectories over the years. Ethnicity (being a Pacific child) followed by deprivation demonstrated stronger relationships with childhood ASH than the geography and the health system input variables.Conclusion The variation in childhood ASH is explained only minimal at the DHB level. The sociodemographic variables also only partly explained the variations. Unlike the general ASH measure, the childhood ASH used in this analysis provides insights into the acute conditions sensitive to primary care services. However, further information would be required to conclude this as the DHB-level performance variations.